2005
DOI: 10.1007/s00425-005-0160-5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant responses to enhanced generation of superoxide anion radical and hydrogen peroxide in the copper-stressed mulberry plants

Abstract: The aim of the study was to implicate the generation of reactive oxygen species (ROS) and altered cellular redox environment with the effects of Cu-deficiency or Cu-excess in mulberry (Morus alba L.) cv. Kanva 2 plants. A study of antioxidative responses, indicators of oxidative damage and cellular redox environment in Cu-deficient or Cu-excess mulberry plants was undertaken. While the young leaves of plants supplied with nil Cu showed chlorosis and necrotic scorching of laminae, the older and middle leaves of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
85
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 38 publications
13
85
0
2
Order By: Relevance
“…However, the activity tends to decrease at longer exposure (14 days) at the highest Cu concentration. Several authors have reported an increase in SOD activity with Cu stress in Morus alba (Tewari et al 2006) and Elsholtzia splendens (Peng et al 2006). Similar results were also observed in GPX activity.…”
Section: Discussionsupporting
confidence: 72%
“…However, the activity tends to decrease at longer exposure (14 days) at the highest Cu concentration. Several authors have reported an increase in SOD activity with Cu stress in Morus alba (Tewari et al 2006) and Elsholtzia splendens (Peng et al 2006). Similar results were also observed in GPX activity.…”
Section: Discussionsupporting
confidence: 72%
“…2A and 2B). Similar results were observed in Phaseolus vulgaris (Bouazizi et al, 2010), Morusalba (Tewari et al, 2006), Beta vulgaris (Henriques, 1989) and Nicotiana tabacum (Raeymaeker et al, 2003). H 2 O 2 acts as a signal in response to plant stress and in supra-optimal concentrations becomes toxic to membranes, affecting its permeability, which can lead to cell death (Soares et al, 2016;Capaldi et al, 2015).…”
Section: Discussionsupporting
confidence: 72%
“…Heavy metals present at elevated levels may cause an increased production of reactive oxygen species (ROS) in plant cells on one hand [42][43][44][45][46][47][48][49][50][51] and may be involved in the enzymatic detoxification of ROS on the other hand [2,3,42,[52][53][54]. Stresses (e.g., drought, heat and high light intensity) may also cause an accumulation of ROS and of ROS-damaged cell constituents [54,55].…”
Section: Heavy Metals: Micronutrients or Pollutants?mentioning
confidence: 99%